Migration, Agriculture and Rural Development IMISCOE Short Reader - Nori, Michele (IMISCOE Research Series, 2020)
This open access short reader looks into the dynamics which have reshaped rural development and human landscapes in European agriculture and the role of immigrant people. Within this framework it analyses contemporary rural migrations and the emergence of immigrants in relation to the incorporation of agrarian systems into global markets, the European agricultural governance (CAP), and the struggle of local territories as differentiated practices in constant stress between innovation and resilience. It specifically explores the case of immigrant shepherds to describe the reconfiguration of agriculture systems and rural landscapes in Europe following intense immigration and the related provision of skilled labour at a relatively low cost. Being written in a very accessible way, this reader is an interesting read to students, researchers, academics, policy makers, and practitioners.